DAYA SIMPAN BUAH MANGGIS (Garcinia mangostana L.) PADA PERLAKUAN PELAPISAN - Luluk Prihastuti Ekowahyuni (Universitas Nasional, 2016)
Mangosteen (Garcinia mangostana L.) is a beneficial fruit that become one of Indonesia's top exported fruit. The fruit peel contains xanthone which is can be used to lower blood sugar level and as an antioxidant. The problem is how to prolong the shelf life with the best fruit condition. One attempt to solve this problem is coating treatment. The objective of this research was to analyze the effect of various concentration of natural beet dying and bee wax emulsion which is used as coating materials on the shelf life of mangosteen fruit. This research was done on March until April 2016 at the Laboratory of Nasional University. The coating applied to this experiment were beet extract 65%, beet extract 75%, beet extract 85%, bee wax 4%, bee wax 6%, and bee wax 8%. Parameter absorved in this research were weight loss, total acid, total soluble solid, and fruit peel color. This treatment significantly affected all of the parameters.The result of BNT test showed the coating material of which the longest shelf life is resulted by maintaining the best fruit condition was bee wax emulsion 8% with weight loss of 8,29%, total acid of 4,4%, total soluble solid of 17,29 °Brix. The result of Dunn test showed best coating material on fruit peel discoloration parameter was beet extract 85% with a score of 8.